Mutations in the TSC1 gene account for a minority of patients with tuberous sclerosis. Issue 12 (December 1998) - Ali, J B; Sepp, T; Ward, S; Green, A J; Yates, J R
Abstract : Tuberous sclerosis (TSC) is an autosomal dominant disorder characterised by tumour-like malformations (hamartomas) of the brain, skin, and other organs, often associated with seizures and learning disability. There is genetic heterogeneity with loci for TSC on chromosomes 9q34 (TSC1) and 16p13.3 (TSC2). The recently cloned TSC1 gene has 23 exons spanning some 40 kb of genomic DNA with an 8.6 kb transcript. We now report the results of mutation screening by SSCP and heteroduplex analysis of genomic DNA for all 21 coding exons of TSC1 in 83 unrelated cases of tuberous sclerosis. TSC1 gene mutations were found in 16 of the 83 cases (19%). These comprised base substitutions, small insertions, or small deletions giving rise to six nonsense mutations, eight frameshifts, and two splice site mutations, all of which would be expected to result in a truncated or absent protein. In the 10 cases predicted to have TSC1 mutations by linkage analysis or loss of heterozygosity studies, the mutation was identified in eight (80%). In the remaining 73 unassigned cases, only eight mutations were found (11%). From these data we estimate that TSC1 mutations accounted for 24% of the cases in this sample (and an estimated 22% of all TSC cases). This contrasts with data from linkage studies suggesting that TSC1 and TSC2 mutations account for approximately equal numbers of families.